Bi primitive switching crypto system with key generation mechanism for secure applications - Ruhan Bevi, A.; Malarvizhi, S. (Journal of the Chinese Institute of Engineers, 2014)
Ensuring security to the information transaction is a major challenge in the communication environment. The choice to guarantee the data transfer using a ciphering algorithm leads to high cost and complexity. The software-based implementations of cryptographic algorithms are easy to design and operate, but the performance penalty paid is high. The hardware implementations of cryptographic algorithms are considered as a task involving intensive computation and evaluation. Microcontroller-based applications for the same prove to be good solutions to the problem for cost-optimized applications. This paper aims to design, implement, and test a microcontroller (AT89c51)-based crypto system using the Tiny Encryption Algorithm and the Extended Tiny Encryption Algorithm as security primitives. The real-time data can be processed with scheduling of the primitives and the context switching between the primitives reduces the probability of being attacked. The keys for the crypto system are generated using internal timers of the microcontroller. The data to be transmitted are encrypted with any one of the security primitives with the generated key and the encrypted data are transmitted both in wired and wireless modes. At the receiving end, the received data are decrypted and the performance of the crypto system is evaluated on the basis of throughput, code size used, and execution time.